The Functional Role of Voltage-Gated Sodium Channel Nav1.5 in Metastatic Breast Cancer - Luo, Qianxuan; Wu, Ting; Wu, Wenfang; Chen, Gong; Luo, Xuan; Jiang, Liping; Tao, Huai; Rong, Mingqiang; Kang, Shuntong; Deng, Meichun (Frontiers in Pharmacology, 2020)
Voltage-gated sodium channels (VGSCs) which are abnormally expressed in various kinds of cancers such as breast cancer, prostate cancer, lung cancer and cervical cancer are involved in the metastatic process as invasion and migration. Nav1.5 is a pore -forming α subunit of VGSC encoded by SCN5A gene. Various studies have demonstrated that Nav1.5, often as its neonatal splice form, is highly expressed in metastatic breast cancer cells. Abnormal activation and expression of Nav1.5 trigger a variety of cellular mechanisms including changing H+ efflux, promoting Epithelial-to-Mesenchymal Transition (EMT) and regulating the expression of cysteine cathepsin, to potentiate the metastasis and invasiveness of breast cancer cells in vitro and in vivo. This paper systematically demonstrates the latest available data on the pro-metastatic effect and the underlying mechanisms of Nav1.5 on breast cancer. We summarize the factors impacting Nav1.5 expression in breast cancer cells, and the recent data on the potential of Nav1.5 blockers serving as candidates for breast cancer treatment are addressed in the review.